2019
DOI: 10.1111/evo.13752
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of male and female mating preferences inDrosophilaspeciation*

Abstract: The relative importance of male and female mating preferences in causing sexual isolation between species remains a major unresolved question in speciation. Despite previous work showing that male courtship bias and/or female copulation bias for conspecifics occur in many taxa, the present study is one of the first large‐scale works to study their relative divergence. To achieve this, we used data from the literature and present experiments across 66 Drosophila species pairs. Our results revealed that male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…Previous studies that address reinforcement in both sexes provide conflicting support for whether male or female preferences are more strongly affected. One study in Drosophila found that while male and female preferences were widespread, female preferences were primarily responsible for isolation between species in sympatry (Yukilevich & Peterson, ). That result is consistent with basic sexual selection theory, which assumes that females invest more heavily in reproduction than males and would pay a higher cost for maladaptive mate choice (Andersson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that address reinforcement in both sexes provide conflicting support for whether male or female preferences are more strongly affected. One study in Drosophila found that while male and female preferences were widespread, female preferences were primarily responsible for isolation between species in sympatry (Yukilevich & Peterson, ). That result is consistent with basic sexual selection theory, which assumes that females invest more heavily in reproduction than males and would pay a higher cost for maladaptive mate choice (Andersson, ).…”
Section: Discussionmentioning
confidence: 99%
“…An effective way to address this question empirically is with comparative studies that quantify male and female preferences for conspecifics across multiple species pairs within a lineage, but these studies are rare. A recent study by Yukilevich and Peterson (), for example, found that both male preference and female preference for conspecific mates are widespread in Drosophila ; however, in species that are sympatric with respect to a close congener, female preferences for conspecifics were stronger than male preferences, suggesting that reinforcing selection primarily acts upon female preferences in sympatry. In contrast, in a study of the darter subgenus Oligocephalus , male preferences showed a signature of reinforcement, being stronger for conspecifics in sympatric versus allopatric populations, whereas female preferences for conspecific males were not significant in either sympatric or allopatric populations (Moran & Fuller, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Yukilevich and Peterson () used pairs of sixteen species groups within the subgenera of Drosophila and Sophophora to identify sex‐specific rates of divergence in mating preferences and sex‐specific contributions to sexual isolation. Yukilevich and Peterson () aggregated their experimentally obtained male courtship and female copulation data with data from prior literature to analyze 66 and 34 species pairs, respectively. They found that males generally tended to be less particular in choosing females for courtship, whereas females were more stringent in copulation preferences and favored copulation with conspecifics.…”
mentioning
confidence: 99%
“…In this issue, Yukilevich and Peterson (2019) used pairs of sixteen species groups within the subgenera of Drosophila * This article corresponds to Yukilevich, R., and E. K. Peterson. 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation